Recent advances on computational analysis of PV/T collectors: A comprehensive review - Kiyak, Burak; Biswas, Nirmalendu; Oztop, Hakan F.; Selimefendigil, Fatih (Pergamon-Elsevier Science Ltd, 2026)
Solar energy technologies are developing day by day with developing on energy material science. It is important for applications of multigeneration systems, including wind, biomass, biogas and hydrogen energy, to supply electricity, domestic hot water and hot clean air. Design of these systems requires simulation before and after experimental design or commercial prototype. Thus, this study illustrated the recent applications and advances on Computational Fluid Dynamics (CFD) and heat transfer principles, including industrial applications. CFD is a useful method to investigate the thermal and fluid dynamics, which could improve performance through a better understanding of the PV/T system. The present review integrated the recent advances in CFD-based modeling of PV/T systems with the emphasis on their role in enhancing thermal efficiency, fluid flow behavior and energy performances of PV/T systems. The paper starts by discussing the basis of operation of PV/T collectors, and their coupling between photovoltaic and thermal production processes, and then elaborates on the CFD modalities adopted in their numerical modeling. Key developments of numerical methods for modeling heat transfer, fluid dynamics and multi-phase interactions are reviewed, highlighting that high-fidelity modeling is essential to ensure accurate performance predictions. The advancements achieved in PV/T collector design, flow distribution, and thermal regulation, made possible through CFD simulation methods, are also reviewed. Such developments respond to challenges like heat dissipation, non-uniform fluid flow, and collector overheating. Additionally, a critical assessment of the role of CFD in investigating novel PV/T configurations, such as hybrid systems and passive cooling, is undertaken. Additionally, the paper discusses the use of experimental data to validate CFD models, highlighting the necessity of improvements in several aspects in order to achieve more reliable models. Although CFD has its advantages, the applications of CFD in PV/T systems are commonly affected by high computational requirements, model complexity, and the necessity for simulations that will accurately represent the real environmental experiences of PV/T collectors. Lastly, the review ends by proposing future research trends, such as artificial intelligence, multi-physics, and real-time CFD simulation for monitoring PV/T systems. This compilation provides a succinct review of the recent progress of PV/T technology using CFD and serves as a handy reference for researchers and engineers to capitalize on CFD for innovating more effective PV/T systems.
Keywords: Pv/T Collectors; Solar Energy; Heat Transfer; Simulation; Energy Efficiency